EMERGENCE OF NEW STRAINS OF SARS-COV-2: AFRICA’S FATE AND ITS PREPAREDNESS AGAINST COVID-19 INFECTION WAVES - Chinenyenwa M.D, Ohia; Solomon, Bakarey Adeleye; Tauseef, Ahmad; Haroon, Haroon; Godson R. E. E., Ana; Mynepalli K.C., Sridhar (African Journal of Infectious Diseases (AJID), 2022)
Background: Severe acute respiratory syndrome coronavirus-2(SARS-CoV-2) has infected over 100million individuals worldwide with diverse impacts on nations. The rising cases of new strains and resultant infection waves create an urgent need to assess the readiness of countries especially in Africa to mitigate the impact on community transmission. This paper delivers a brief synopsis of the novel SARS-CoV-2, emerging cases of new variants reported worldwide, and implications for genetic surveillance of disease transmission in low-and middle-income countries (LMICs) especially Africa. Materials and Methods: Literature search used keywords like SARS-CoV-2; COVID-19 epidemiology; pandemic waves; corona outbreak, clinical syndromes, treatments, prevention and control. Cross-sectional and observational studies published on COVID-19 from 2019 till date of study provided main information sources. Databases such as Web of Science, Embase, PubMed and Google Scholar were utilised. Main findings: Over 220 countries have documented COVID-19 cases with varied severity till date. Before the spikes in resurgence, a highly virulent mutated (>90% fatality rate) novel strain of COVID-19 had been documented. There is very little data to ascertain the impact of the COVID-19 infection waves in LMICs. Discussion: LMICs especially African countries still grapple with significant challenges like inefficient surveillance mechanisms, inadequate vaccination coverage, inadequate enforcement of environmental health strategies, poor health systems etc. Hence, Africa’s fate remains dicey in the face of the dynamic evolution of the SARS-CoV-2 and other identified challenges. Conclusion: The adoption of a multidisciplinary approach to mitigate the impact of emergence of mutant SARS-CoV-2 variants and resurgence of infection spike is recommended